Unemployment, total factor productivity, budget deficit, and wage share in South Africa - Juniours Marire (Universitas Islam Indonesia, 2022)
Purpose ― The paper investigated the effect of the interaction of fiscal deficits and total factor productivity (TFP) and fiscal deficits and the wage share on unemployment. Methods ― The paper applied an autoregressive distributed lag model to South African annual data from 1991-2019. Findings ― First, increases in fiscal deficits increase unemployment at all levels of TFP and wage share. Second, increases in TFP increase unemployment at different levels of fiscal deficit, but after the global economic recession, the rate of increase in unemployment declined significantly. This means that the interaction of rising TFP and fiscal deficits in South Africa, where the growth regime is profit-led and technology-driven, always results in increasing unemployment. Third, as the wage share increases, unemployment increases, at all levels of fiscal deficits, suggesting that a wage-led growth regime is no panacea to unemployment either. Implications ― The findings imply that expansionary fiscal policy does not necessarily create an economy that works for all unless active labour market institutions are set up. The findings challenge the notion that the solution to unemployment in South Africa is wage flexibility. Neither do the findings support the idea that following a profit-led growth path is a solution. A balanced mix of the two growth regimes would work. Originality ― Studies have considered the productivity-enhancing effects of structural fiscal policy, but they have not considered the possible effects of interactions between productivity, fiscal policy and wage shares. The paper addresses the gap by introducing the interactions of TFP and fiscal deficits, as well as the interaction of wage share and fiscal deficits.